Lay knowledge about madness and mental illness - Alves, Fátima (2020)
The way in wich societies relate to madness is in accordance with dominant concepts about the world (Benedict, 1934; Devereux, 1970). Modern rationality has created mental illness as an ‘object’ controlled by medicine (Foucault, 1987).The concepts, attitudes and practices associated with mental illness in modern societies are different in the scientific universe of psychiatry and in the lay universe that is culturally distant from the scientific representation of the body, the disease and the patient (Devereux, 1970). There is some knowledge about social exclusion processes contributing to the construction of mental illness. However they mainly focus on social representations (De Rosa, 1987; Serino, 1987; Jodelet, 1995) and the public image (Cummings and Cummings, 1957; Nunnaly, 1961; Philips, 1966; Bhugra, 1989; G.U.M.G., 1994; Philo et al., 1996) while ignoring the perspective of sufferers and their relatives. The semi-peripheric condition of Portuguese society is the factor which allows characteristics typical of developed societies to co-exist on a par with characteristics typical of less developed and less complex societies (Santos, 1990). This situation leads us to believe that inside the more universal system of modernity, the explanation of insanity and mental illness in Portuguese society contains some specifics. Some relevant aspects of this are: 1 – The ‘psychiatrization’ of Portuguese society is incomplete as the welfare state was only recently and partialy established, resulting in the almost non-existence of community structures, thus the social integration of mentally ill is the responsibility of the family (Alves, 1998). 2 – In Portuguese society where democracy was introduced relatively recently, civic participation is low which can be seen in the low level of lay people’s criticism of medicine. 3 – Rurality is still a defining factor in people’s way of thinking and it contributes to the pre-modern reference system. The study that we present here centres on the lay knowledge system in explaining mental illness. In this context we try to understand to what level the common universe of perceptions, attitudes and practices associated with mental illness has been penetrated by psychiatry. What other thought and action systems apart from this, can people turn to? Our report is the result of the analysis of information gathered